Medicinal Plant-Derived Exosome-Like Nanovesicles as Regulatory Mediators in Microenvironment for Disease Treatment - Feng Z; Huang J; Fu J; Li L; Yu R; Li L (International Journal of Nanomedicine, 2025)
Zhiying Feng,1,* Jiawang Huang,1,* Jingmin Fu,1 Lixin Li,2 Rong Yu,1 Ling Li3 1College of Traditional Chinese Medicine of Hunan University of Chinese Medicine, Changsha, Hunan, 410208, People’s Republic of China; 2College of Medicine of Hunan University of Chinese Medicine, Changsha, Hunan, 410208, People’s Republic of China; 3College of Integrated Traditional Chinese and Western Medicine of Hunan University of Chinese Medicine, Hunan, Changsha, 410208, People’s Republic of China*These authors contributed equally to this workCorrespondence: Ling Li, Email liling1049@hnucm.edu.cn Rong Yu, Email yurong196905@163.comAbstract: Medicinal plant-derived exosome-like nanovesicles is a kind of vesicles with a diameter of 30– 300 nm extracted from medicinal plants, which can regulate the microenvironment of various systems, diseases and cells through multiple drug delivery routes, so as to achieve the purpose of alleviating and treating diseases. In this paper, the extraction and identification methods of nanovesicles derived from medicinal plants were summarized. Then, according to the systematic classification of diseases, the effects and mechanisms of the treatment of diseases and the regulation of the microenvironment by the nanovesicles derived from medicinal plants were summarized and analyzed. This paper finds Medicinal plant-derived exosome-like nanovesicles, as plant-derived nanoscale vesicles, can act more efficiently on various microenvironments of the body such as inflammation, tumors, immunity and the intestine through various administration methods such as oral administration and intravenous injection according to the characteristics of the disease, achieving the effect of treating diseases and alleviating symptoms. Medicinal plant-derived exosome-like nanovesicles have initiated a new model of transboundary communication regulation involving plants in the human microenvironment, using their own advantages to regulate the human microenvironment. Meanwhile, it can also be used as a drug carrier to achieve a dual communication regulation effect. It provides ideas for the follow-up research and clinical use of nanovesicles derived from medicinal plants. Keywords: medicinal plants, nanovesicles, microenvironment, systemic disease mechanism